Analisis Tingkat Pendapatan Usahatani Padi Sawah pada Sistem Tanam Jajar Legowo dan Sistem Tanam Non Legowo di Kecamatan Indrapuri Kabupaten Aceh Besar - Dinda Maristha; Monalisa Monalisa; Teuku Makmur (Jurnal Ilmiah Mahasiswa Pertanian, 2022)
Rice (Oryza sativa) is an important food crop that has become the staple food of more than half of the world's population. This study aims to determine the level of income and analysis of revenues and costs (R/C ratio) of lowland rice farming using the row legowo planting system and lowland rice farming using the non-legowo cropping system in Indrapuri District, Aceh Besar. Respondents used as samples in this study were lowland rice farming using the row legowo planting system and lowland rice farming using the non-legowo cropping system 38 people in Indrapuri District, Aceh Besar. The results showed that the average income of lowland rice farming using the jajar legowo planting system was higher than the income of lowland rice farming using the non-legowo cropping system. The value of R/C ratio for lowland rice farming with jajar legowo planting system is 2.60 which indicates that Rp. 2.00 the costs incurred in rice farming with the jajar legowo planting system will get an income of Rp. 2.60. Meanwhile, for lowland rice farming that applies the non-legowo cropping system, the R/C ratio is 1.67 which shows that every Rp. 1.00 expenses incurred will get an income of Rp. 1.67.